Correlation between vancomycin penetration into cerebrospinal fluid and protein concentration in cerebrospinal fluid/serum albumin ratio. Issue 2 (February 2019) - Ishikawa, Masayuki; Yamazaki, Shingo; Suzuki, Takaaki; Uchida, Masashi; Iwadate, Yasuo; Ishii, Itsuko
Abstract: Bacterial meningitis is a life-threatening condition. Vancomycin (VCM) is one of the antibiotics used as empirical therapy for bacterial meningitis. It is essential to maintain an adequate concentration of VCM in cerebrospinal fluid (CSF) to treat bacterial meningitis effectively. VCM administered intravenously must pass the blood-brain barrier (BBB) to enter the CSF and the extent of VCM penetration into CSF varies widely among patients. Previous report indicated that CSF albumin level is useful for estimation of VCM CSF penetration. However, CSF albumin level is not measured in routine practice. We focused on CSF protein concentration that is generally examined at the beginning of diagnosis and treatment of bacterial meningitis. We examined the relationship between CSF protein concentration/serum albumin ratio and the extent of VCM penetration into CSF. This retrospective study involved 7 patients admitted to our hospital who were treated with VCM for suspected bacterial meningitis. The VCM concentrations in serum and CSF were 17.6 ± 7.2 μg/mL and 3.31 ± 3.14 μg/mL, respectively. The serum VCM concentrations showed no significant correlation with CSF VCM concentrations. On the other hand, the protein concentration in CSF/serum albumin ratio showed a strong positive correlation with the VCM CSF/serum ratio ( r  = 0.877, p  < 0.005). Our study indicates that the ratio of CSF protein concentration/serum albumin is likely useful for estimating the approximate VCM CSF/serum ratio. This could contribute to an improvement in the treatment of bacterial meningitis.